The Effect of Anemia Education on Increasing Haemoglobin Levels in Adolescent Girls - Millenia, Silva; Rahmadyanti, Rahmadyanti (Indonesian Journal of Global Health Research, 2024)
The high incidence of anemia in adolescent girls can affect various impacts of growth and development. So that learning achievement decreases, physical endurance is low so easily tired, physical activity decreases, easily sick due to low body resistance, one of the prevention that can be made in reducing the incidence of anemia in adolescent girls is to give the education for increasing knowledge about anemia. The purpose of the study was to analyze the effect of education about anemia and nutrition on increasing haemoglobin levels in female students. This study was an experimental quasy design. at SMPN 1 Jasinga, Pamegarsari village, Jasinga District, Bogor Regency, West Java Province from September to January 2024. The sample was 146 female students, sampling was done by simple random sampling technique. Data was collected by direct hemoglobin examination. Bivariate analysis is with the Mann Whitney U test. The results of the Mann-Whitney test where in pairs before the intervention and after the intervention obtained Sig.2-tailed values of 0.004 < 0.05, it can be concluded that there is a difference in average haemoglobin levels before and after education.